2020
DOI: 10.3390/nano10061155
|View full text |Cite
|
Sign up to set email alerts
|

Resistive Switching Property of Organic–Inorganic Tri-Cation Lead Iodide Perovskite Memory Device

Abstract: In this study, a glass/indium tin oxide (ITO)/formamidinium-methylammonium-cesium (FA-MA-Cs) tri-cation lead iodide perovskite/poly(methyl methacrylate (PMMA)/Al memory device with a controlled composition of (FA0.75MA0.25)1-xCsxPbI3 (x = 0–0.1) is demonstrated to exhibit bipolar resistive switching behavior. The tri-cation organic–inorganic metal halide perovskite film was prepared by a one-step solution process in which the amount of Cs was varied to modify the property of FA0.75MA0.25PbI3. It was found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Moreover, a recent study revealed that V I is located in GBs within the perovskite film, which is consistent with our C-AFM results. Furthermore, several theoretical and experimental studies have shown that perovskite GBs serve as channels for ion migration. ,, Therefore, we believe that it is possible to migrate to the anode/Au interface under an applied bias with I – ions, which can generate V I along GBs in the perovskite film. However, we did not observe memory characteristics in FA-rich FAMAPbI 3 .…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Moreover, a recent study revealed that V I is located in GBs within the perovskite film, which is consistent with our C-AFM results. Furthermore, several theoretical and experimental studies have shown that perovskite GBs serve as channels for ion migration. ,, Therefore, we believe that it is possible to migrate to the anode/Au interface under an applied bias with I – ions, which can generate V I along GBs in the perovskite film. However, we did not observe memory characteristics in FA-rich FAMAPbI 3 .…”
Section: Resultsmentioning
confidence: 94%
“…However, when the applied voltage was further increased to 0.97 V, the current in the device abruptly increased from 10 –3 to 10 –1 A. This sweep represents the region in which the resistance switched from the HRS to the low-resistance state (LRS) . This clearly indicates that the FAMAPbI 3 device switches from the off state to the on state.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…However, the PL peak of CsBr-15s is close to that of CsBr-10s due to the needle-like structure of part of the other phase. The PL is sensitive to defects in OIHP films, and higher peak intensities are associated with fewer defects . In addition, when the post-treatment process of ionic modification was applied on the MAPbI 3 film surface, the trap states on the perovskite film surface were passivated, and the energy band structure was altered compared to that of the OIHP film without interfacial modification. ,, Figure d presents the ultraviolet–visible (UV–vis) absorption spectra of MAPbI 3 with and without the post-treatment process, with all of the samples of the OIHP showing similar identical absorption edges in the 400–800 nm range.…”
Section: Resultsmentioning
confidence: 99%
“…The organic materials have potential aspirant for future device applications. 1,2 For example, light-emitting diodes, [3][4][5][6] transistors, [7][8][9][10] photo voltaic cells, [11][12][13][14][15] and switches, [16][17][18][19][20] have been realized. However, one of the important electronic devices is memory which will provide or store the information for logic operation.…”
Section: Introductionmentioning
confidence: 99%